2011
DOI: 10.1210/jc.2010-1588
|View full text |Cite
|
Sign up to set email alerts
|

Age at Diagnosis of Pheochromocytoma Differs According to Catecholamine Phenotype and Tumor Location

Abstract: The variations in ages at diagnosis associated with different tumor catecholamine phenotypes and locations suggest origins of PPGLs from different chromaffin progenitor cells with variable susceptibility to disease causing mutations. Different optimal age cut-offs for mutation testing are indicated for patients with and without epinephrine-producing tumors (44-49 vs. 30-35 yr, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 28 publications
6
48
0
1
Order By: Relevance
“…In our patient, nor-epinephrine production was higher than epinephrine. This finding is in line with studies that in patients with negligible epinephrine-producing tumors, age at diagnosis was earlier than in epinephrine-producing tumors 12,13. Computed tomography can localize the adrenal tumors, and MRI is superior for the detection of extra-adrenal tumors.…”
Section: Discussionsupporting
confidence: 90%
“…In our patient, nor-epinephrine production was higher than epinephrine. This finding is in line with studies that in patients with negligible epinephrine-producing tumors, age at diagnosis was earlier than in epinephrine-producing tumors 12,13. Computed tomography can localize the adrenal tumors, and MRI is superior for the detection of extra-adrenal tumors.…”
Section: Discussionsupporting
confidence: 90%
“…A recent report by Zelinka et al [9] combined DA-secreting tumors with non-secretory tumors but found no difference between benign and malignant tumors. The probable reason for this may be the low number of patients with SDH-B mutations in their patient population (N = 2); such tumors are associated with both higher percentage of malignancy and DAsecreting/silent tumors [34][35][36][37][38]. The group of malignant DA-secreting/silent tumors did, however, show a significantly decreased survival in this study, exhibiting a 5-year survival of around 50% [9].…”
Section: Biochemistrymentioning
confidence: 57%
“…As described previously (15), adrenaline-producing tumours were defined by both increased plasma concentrations of metanephrine above the upper cut-offs (88 pg/ml, 0.45 nmol/l) and increases in metanephrine larger than 5% of the combined increases in both plasma normetanephrine and metanephrine. The latter was defined by the equation %MN t Z((MN t )/(NMN t CMN t ))!…”
Section: Definition Of Adrenaline-producing Ppglsmentioning
confidence: 99%
“…100 where MN t and NMN t are tumour-derived plasma concentrations of metanephrine and normetanephrine. As described previously (15), tumour-derived concentrations were determined by subtracting mean concentrations in a reference population of patients without PPGLs from measured concentrations in patients with PPGLs.…”
Section: Definition Of Adrenaline-producing Ppglsmentioning
confidence: 99%